Protecting health from climate change : global research priorities (WHO GenevaCH, 2009)
Presents the conclusions and recommendations emanating from the global consultation organised by the Public Health and Environment Department of the World Health Organization and a subsequent meeting hosted by the Spanish Ministry of Health from 6 - 8 May 2008. Aims at improving the evidence base for policies to protect health from climate change.
References p. 20-21